Rifting processes and ice-flow modulation observed on Mertz Glacier, East Antarctica. Issue 230 (2015) - Lescarmontier, L.; Legresy, B.; Young, N.W.; Coleman, R.; Testut, L.; Mayet, C.; Lacroix, P.
Abstract: We investigated the evolution of two major rifts cutting across Mertz Glacier Tongue, East Antarctica, using a combination of satellite images and 60 day sets of GPS data from two stations deployed either side of the western rift in 2007. The eastern rift began to open in the early 1990s, and the western rift initiated in 2002 in conjunction with the collision of a large iceberg with the tongue. Velocity time series derived from the 2007 GPS data exhibited strong variations at tidal periods modulated by sea-surface height and sea-surface slope and reproduced here with a conceptually simple model. We found that opening of the western rift in 2002 leads to a dramatic change in behavior of the tongue as the large range in velocity (700–2400 m a −1 ) observed in 2000 was largely reduced (1075–1225 m a −1 ) in 2007. Opening of the western rift decoupled the glacier from the transverse loading on the tongue driven by east–west tidal circulation. This loading previously induced time-varying lateral drag, which caused the large velocity range. Our results suggest changes in the mechanical behavior of an ice tongue impact the dynamics of the outlet glacier system and should be considered in longer-term mass-balance evaluations.